MENUMBUHKAN KARAKTERISTIK RELIGIUS DAN EMPATI SISWA MELALUI CERITA NABI DALAM PELAJARAN PAI DI SDN 1 LALONGGASUMEETO - Futry Ayu Lestari; Nur Hidayat; Widyawati (STKIP Subang, 2025)
Islamic Religious Education (PAI) in elementary schools plays a vital role in fosteringstudents’ religious and empathetic character. This study investigates theeffectiveness of prophetic stories as a teaching method in PAI at SDN 1Lalonggasumeeto, Konawe, Southeast Sulawesi, to cultivate these traits. Using aqualitative case study design, the research involved 25 fifth-grade students and a PAI teacher. Data were collected through unstructured observations, semi-structured interviews, and documentation, analyzed using Miles and Huberman’s model of data reduction, presentation, and conclusion drawing, with sourcetriangulation for validity. Results show that stories of Prophet Muhammad SAW andProphet Yusuf AS enhance students’ religious practices, such as consistent prayerand supplication, and foster empathy through actions like sharing and reducedbullying. Challenges, including limited time and technology, were addressed throughteacher creativity and community collaboration. This study provides insights for PAIteachers to develop contextual, narrative-based learning in rural settings.